THE ROLE OF ARTIFICIAL INTELLIGENCE IN DEVELOPING MEDICAL STUDENTS’ CLINICAL REASONING SKILLS - Rahimova Fotima; Maksudova Malika; Nadirova Yulduz (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. The rapid development of artificial intelligence (AI) has significantly influenced medical education, particularly in the enhancement of clinical reasoning skills among medical students. Clinical reasoning is a core competency required for accurate diagnosis, effective decision-making, and safe patient care. This paper explores the role of AI-driven educational technologies in supporting and enriching the learning experience of medical students. AI-based tools such as intelligent tutoring systems, virtual patients, clinical decision support systems, and learning analytics are analyzed in terms of their pedagogical value. The study highlights the benefits, challenges, and future prospects of integrating AI into medical curricula, emphasizing its potential to foster individualized learning, improve diagnostic accuracy, and bridge the gap between theory and clinical practice.